2015
DOI: 10.1177/0284185115598808
|View full text |Cite
|
Sign up to set email alerts
|

CT texture analysis can help differentiate between malignant and benign lymph nodes in the mediastinum in patients suspected for lung cancer

Abstract: CT texture analysis can help differentiate between malignant and benign lymph nodes in the mediastinum in patients suspected for lung cancer Abstract BackgroundIn patients with Non-Small-Cell Lung Carcinoma NSCLC the lymph node staging in the mediastinum is important due to impact on management and prognosis. Computed tomography texture analysis (CTTA) is a post processing technique that can evaluate the heterogeneity of marked regions in images. PurposeTo evaluate if CTTA can differentiate between malignant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 22 publications
2
76
2
Order By: Relevance
“…The SVMs performed equivalently to quantitative SUV max and mean nodal short-axis diameter in diagnosing malignant thoracic lymph nodes. In another study, the mean attenuation measurement was shown to be useful in predicting nodal metastasis in lung cancer patients (n = 46) [31]. The authors found a mean difference of 20 HU between benign and malignant lymph nodes.…”
Section: Imaging Heterogeneity In Lung Cancermentioning
confidence: 95%
See 1 more Smart Citation
“…The SVMs performed equivalently to quantitative SUV max and mean nodal short-axis diameter in diagnosing malignant thoracic lymph nodes. In another study, the mean attenuation measurement was shown to be useful in predicting nodal metastasis in lung cancer patients (n = 46) [31]. The authors found a mean difference of 20 HU between benign and malignant lymph nodes.…”
Section: Imaging Heterogeneity In Lung Cancermentioning
confidence: 95%
“…Nevertheless, studies investigating texture analysis as a potential classification tool are showing promising results, and it is hoped that texture analysis may improve the accuracy of imaging [23,[30][31][32][33].…”
Section: Applications In Lesion Classificationmentioning
confidence: 99%
“…Chest.-CTTA has also been applied to differentiating benign from malignant entities in the chest. It has been used to differentiate benign from malignant pulmonary nodules and mediastinal lymph nodes (3,(31)(32)(33)(34) and to differentiate radiation fibrosis from recurrent lung cancer (3,35,36).…”
Section: Lesion Characterizationmentioning
confidence: 99%
“…Given that knowledge, there has also been investigation into the textural features of tumors outside of the primary site. CT textural features were recently shown to be correlated with malignant and benign lymph nodes 26,27 . However, to date there have been very few quantitative analyses of NSCLC lymph node features correlated with clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%